IMPLEMENTASI KEBIJAKAN PERATURAN DAERAH NOMOR 8 TAHUN 2014 TENTANG PENGELOLAAN SAMPAH KOTA PEKANBARU (STUDI KASUS KECAMATAN TAMPAN) - Sinaga, Putri Irna Dessih; Harahap, Tuti Khairani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Human being is a caused of garbage existance because every human activities produce garbage. The quick Number of Human increasing in city, affected to increasing of garbage. Increasing not following by repairing and developing garbage management infrastructure so that garbage problem be a complexity. Pekanbaru is a quite rapidly developing city not only in infrastructure but alsonumber of population, investment, industry and trading which not free from garbage problem yearly.Highest garbage production founded in Tampan Regency because it’s one of quick population growth so that should take special attention. Pekanbaru Environmental and hygiene services is responsible departement to responsible of garbage management in Tampan Regency. To overcame this problem, government release local regulation (perda) number 8 year 2014 about garbage management. Factly, in Tampan still find much garbage in every side of road long day.The purpose of this research is to know how this local regulation implemented. This research use qualitatif method with descriptif data assesment. In data colecting, researcher use interview technique, observation, and documentation with use key informan as source information.The result of this research reveal that Pekanbaru Environmental and hygiene services already schedule garbage wasting time and serve garbage infrastructure management. But inimplementation, the action is not maximal caused of minimum of infrastructure and less participating from citizen to reach the purpose of policy. Caused of less participating from citizen because minimum or no communication from government to citizen.Keywords : implementation, waste management, Tampan Regency